已知2*8^x*16^x=2^22,求x的值 已知(27^x)^2=3^8,求x的值已知2*8^x*16^x=2^22,求x的值已知(27^x)^2=3^8,求x的值

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/06 08:21:11
已知2*8^x*16^x=2^22,求x的值 已知(27^x)^2=3^8,求x的值已知2*8^x*16^x=2^22,求x的值已知(27^x)^2=3^8,求x的值
x͑MK1ǿʲ ̺^귐FɎ3AD*փ`[C[ m͏il,*^ I_Tt?/l,1=<ޭ$aTc1}Gr<ÃD/n{.Pb`d=>-+@@aݲ+-mr&}}v1ꍞcv,~eY;7s#w+0uxqjooxckk~X

已知2*8^x*16^x=2^22,求x的值 已知(27^x)^2=3^8,求x的值已知2*8^x*16^x=2^22,求x的值已知(27^x)^2=3^8,求x的值
已知2*8^x*16^x=2^22,求x的值 已知(27^x)^2=3^8,求x的值
已知2*8^x*16^x=2^22,求x的值
已知(27^x)^2=3^8,求x的值

已知2*8^x*16^x=2^22,求x的值 已知(27^x)^2=3^8,求x的值已知2*8^x*16^x=2^22,求x的值已知(27^x)^2=3^8,求x的值

x=3 x=2

(1)
2×2^(3x)×2^(4x)=2^22
2^(1+3x+4x)=2^22
1+7x=22
x=3
(2)
(27^-x)^2=[3^(-3x)]^2=3^(-6x)=3^8,因此-6x=8,x=-0.75。
看完了采纳哦~~